2013
DOI: 10.1088/0031-8949/87/02/025702
|View full text |Cite
|
Sign up to set email alerts
|

Third-order harmonics generation in ZnS/CdSe/ZnS cylindrical nanoshells

Abstract: Third-order harmonics generation (THG) has been investigated for ZnS/CdSe/ZnS nanoshell structure. Numerical calculations show that THG susceptibility has two peaks and depends on the parameters such as the size and the kind of structure, the relaxation time and the pump photon energy. The intensity and position of third-order nonlinear susceptibility peaks depend on shell thicknesses; smaller thickness have peak susceptibility at shorter wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…Energy states decrease when the QW shell is enlarged, which is the consequence of a reduced energy interval. Our results are comparable to those of Bahari et al [40] done on a ZnS/CdSe/ZnS cylindrical nanoshell.…”
Section: Resultssupporting
confidence: 91%
“…Energy states decrease when the QW shell is enlarged, which is the consequence of a reduced energy interval. Our results are comparable to those of Bahari et al [40] done on a ZnS/CdSe/ZnS cylindrical nanoshell.…”
Section: Resultssupporting
confidence: 91%
“…Numerous studies were reported about the routes to synthesize mercury sulfide (HgS) nanoparticles (NPs) and quantum dots (QDs) [1][2][3][4][5][6][7][8][9][10][11][12][13]. At the same time, the nonlinear optical (NLO) characterization of HgS QDs and NPs has rarely been reported [14][15][16][17]. The interest in these properties is related to the applications of HgS QDs and NPs as optical limiters, mode-lockers, and Q-switchers.…”
Section: Introductionmentioning
confidence: 99%
“…The third-order nonlinear optical susceptibility induced by the transition between E-1 (inside the well) and E-2 (outside the well) has been calculated for the third harmonic generation (THG) under the effective mass approximation and modified by the local field theory. THG has also been investigated in the ZnS/CdSe/ZnS nanoshell structures [16]. Numerical calculations showed that THG susceptibility has two peaks and depends on parameters such as the size and the kind of structure, the relaxation time, and the pump photon energy.…”
Section: Introductionmentioning
confidence: 99%